2020
DOI: 10.1002/brb3.1660
|View full text |Cite
|
Sign up to set email alerts
|

Trousseau syndrome with intrahepatic cholangiocarcinoma that could be removed radically after endovascular treatment: Report of a case

Abstract: Background Trousseau syndrome is a poor prognosis. We report a case of Trousseau syndrome treated by radical resection after endovascular treatment. Case A 59‐year‐old woman presented to our department reporting spontaneous dizziness and pain of the upper abdomen. Magnetic resolution imaging (MRI) showed shower embolization of Brain. Contrast‐enhanced computer tomography (CT) showed renal infarction and splenic infarction, and a tumor was observed in the retrohepatic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…13,14) In these studies, risk factors of re-occlusion included the number of device passes, missed residual thrombus or stenosis on the past angiography after thrombectomy, intracranial ICA or M2 occlusion, stroke of undetermined cause, and statin pretreatment. 13,14) According to our research, there are 14 reported incidences of TS treated by MT with available literature [2][3][4]13,[15][16][17][18][19][20][21][22] (Table 1). Of half of the cases that experienced re-occlusion of the cerebral large vessels, five cases involved the same vessels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13,14) In these studies, risk factors of re-occlusion included the number of device passes, missed residual thrombus or stenosis on the past angiography after thrombectomy, intracranial ICA or M2 occlusion, stroke of undetermined cause, and statin pretreatment. 13,14) According to our research, there are 14 reported incidences of TS treated by MT with available literature [2][3][4]13,[15][16][17][18][19][20][21][22] (Table 1). Of half of the cases that experienced re-occlusion of the cerebral large vessels, five cases involved the same vessels.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, the difficulty of medical therapy may depend on the progression or state of the primary lesion. 18 , 19) …”
Section: Discussionmentioning
confidence: 99%
“…Splenic infarction in hepatocellular carcinoma was formerly reported in sorafenib use 29 , post transcatheter arterial chemoembolization 30 , and post ethanol ablation 31 . Two recent case reports revealed splenic infarction in cholangiocarcinoma, depicted as Trousseau's syndrome 32 , 33 . There appears to be a high association with the hyper-coagulation system induced by mucin-producing adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%